1982
DOI: 10.1366/0003702824638665
|View full text |Cite
|
Sign up to set email alerts
|

Infrared Laser-Induced Thermal Lens Calorimetry

Abstract: Thermal lens calorimetry is applied to the measurement of infrared absorption of condensed phase samples. The unique trade offs encountered with longer wavelength lasers in thermal lens measurements are discussed. As a demonstration of the technique, the determination of hydrocarbons using a helium-neon laser operated at 3.39 μm is reported. The minimum detectable sample has an absorbance, A = 5 × 10−4, corresponding to 8 ng of 2,2,4-trimethylpentane within the beam volume in the sample. Interpretation of abso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
12
0

Year Published

1984
1984
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…When the beam is unblocked, the time-dependent defocusing of the beam, resulting from the formation of a "divergent" lens inside the sample, is monitored via the intensity change (drop) at the beam center by an oscilloscope (2)(3)(4)(5). For Sensitive detection of small absorbances, a computer is utilized to evaluate the transient lens signals (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17). Using a 160-mW Ar+ laser, Dovichi and Harris have demonstrated a minimum measurable absorbance of 7 X 10"8 (10).…”
mentioning
confidence: 99%
“…When the beam is unblocked, the time-dependent defocusing of the beam, resulting from the formation of a "divergent" lens inside the sample, is monitored via the intensity change (drop) at the beam center by an oscilloscope (2)(3)(4)(5). For Sensitive detection of small absorbances, a computer is utilized to evaluate the transient lens signals (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17). Using a 160-mW Ar+ laser, Dovichi and Harris have demonstrated a minimum measurable absorbance of 7 X 10"8 (10).…”
mentioning
confidence: 99%
“…However, recent findings of an enhanced Raman scattering for various compounds adsorbed at the silver surface (SERS, surface-enhanced Raman scattering) (4,5) give new potential for analytical applications of Raman spectrometry (6). Thus spraying paper chromatograms with silver colloidal solution produces a strong intensity for resonance Raman scatterers from separated dyes (7,8). This surfaceenhanced resonance Raman scattering (SERRS) spectrometry has permitted in situ colored substances down to 2 ng/cm2 to be detected and identified from chromatogram spots (7).…”
Section: Literature Citedmentioning
confidence: 99%
“…On the other hand Bialkowski et al demonstrated ultrasensitive detection of hydrocarbons such as dichlorodifluoromethane, chlorotrifluoromethane, and ethanol by a high-power pulsed C02 laser (5-7). Harris et al also reported the use of an infrared He-Ne laser (3.39 µ ) for determination of 2,2,4-trimethylpentane (8). The C02 laser is line-tunable from 9 µ to 11 µ , so that 0003-2700/87/0359-0523501.50/0 the bar graph spectrum can be measured.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The thermal lens effect, first reported by Gordon et al (1), has been developed into a sensitive, quantitative method for the determination of trace-level samples (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21). Efforts to improve the detection capabilities of this method have primarily been directed toward minimizing the effect of laser intensity fluctuations on the measurement.…”
mentioning
confidence: 99%